Tribological behavior of shape-specific microplate-enriched synovial fluids on a linear two-axis tribometer - Agnese Fragassi; Antonietta Greco; Martina Di Francesco; Luca Ceseracciu; Aiman Abu Ammar; Israel Dvir; Thomas Lee Moore; Haytam Kasem; Paolo Decuzzi (Friction)
Abstract Nano- and micro-particles are being increasingly used to tune interfacial frictional properties in diverse applications, from friction modifiers in industrial lubrication to enhanced biological fluids in human osteoarthritic joints. Here, we assessed the tribological properties of a simulated synovial fluid enriched with non-spherical, poly lactic-co-glycolic acid (PLGA) microparticles (µPL) that have been previously demonstrated for the pharmacological management of osteoarthritis (OA). Three different µPL configurations were fabricated presenting a 20 µm × 20 µm square base and a thickness of 5 µm (thin, 5H µPL), 10 µm (10H µPL), and 20 µm (cubical, 20H µPL). After extensive morphological and physicochemical characterizations, the apparent Young’s modulus of the µPL was quantified under compressive loading returning an average value of ∼ 6 kPa, independently of the particle morphology. Then, using a linear two-axis tribometer, the static (µ s) and dynamic (µ d) friction coefficients of the µPL-enriched simulated synovial fluid were determined in terms of particle configuration and concentration, varying from 0 (fluid only) to 6µ105 µPL/mL. The particle morphology had a modest influence on friction, possibly because the µPL were fully squeezed between two mating surfaces by a 5.8 N normal load realizing boundary-like lubrication conditions. Differently, friction was observed to depend on the dimensionless parameter Ω, defined as the ratio between the total volume of the µPL enriching the simulated synovial fluid and the volume of the fluid itself. Both coefficients of friction were documented to grow with Ω reaching a plateau of µ s ∼ 0.4 and µ d ∼ 0.15, already at Ω ∼ 2×10−3. Future investigations will have to systematically analyze the effect of sliding velocity, normal load, and rigidity of the mating surfaces to elucidate in full the tribological behavior of µPL in the context of osteoarthritis.